De geschiedenis van een herenhuis te Beverwijk (Bulletin KNOB, 2007)
The house Breestraat 101 is situated on the main (shopping) street of Beverwijk and has nevertheless retained the character of a stately 18th-century residence. Traditionally this is a market street, a transshipment site parallel to the shore of the once nearby Wijkermeer. On deep, narrow plots houses with gables were situated here in the 17th century, as can be seen on maps from that period. The present wide premises consists of two plots/houses of which the structure is still recognizable by the double hallway and a cellar with mezzanine room. Lourens Johannes Stelt (1736-1784) was responsible for combining the premises and building the large house. His son Pieter was among the wealthiest inhabitants of Beverwijk, became mayor and must have commissioned the conversion of the interior in the second half of the 18th century. It concerned the hall, the hallway and the front room in which stuccoed ceilings with ornaments in Rococo/ Louis XV style were applied. In this front room there are wooden panelling and mouldings on which five painted wall coverings with idealized Dutch landscapes were applied, as well as grisailles above the five doors, two of which were signed by J.L. Austini (1748- 1822). In the mezzanine room a bureau dating from the same period was built in. The back door is decorated with voluptuous Rococo, because it faced the harbour. Under different proprietors only small changes were carried out in the 19th and 20th century. At present the building functions as a presbytery of the Roman Catholic St.-Agatha church (1922-'24) of architects P.J.H. and J.Th.J. Cuypers. built in the back garden